Firms in (Green) Public Procurement: Financial strength indicators' impact on contract awards and its repercussion on financial strength - Christopher F. Baum; Arash Kordestani; Dorothea Schäfer; Andreas Stephan (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
We examine whether the financial strength of companies, in particular, small and medium-sized enterprises (SMEs) is causally linked to the award of a public procurement contract (PP), especially in the environmentally friendly 'green' area (GPP). For this purpose, we build a combined procurement company data set from the Tenders Electronic Daily (TED) and the SME database AMADEUS, which includes ten European countries. First, we apply probit models to investigate whether the probability of winning the public tender depends on the company's financial strength. We then use the Flexpanel DiD approach to investigate the question of whether the award has an impact on the future financial strength of the successful company. On the one hand, we find that a lower equity ratio and a higher short-term debt ratio increase the probability of being successful in a public tender. On the other hand, the success means that the companies can continue to work after the award with a lower equity ratio than comparable companies without an award, regardless of whether the company was successful in a traditional or a 'green' public tender. We conclude from this that the success in a PP is a substitute for one's own financial strength and thus facilitates access to external financing. The estimation results differ depending on whether public procurement in general or the sub-group of 'green' public procurement is examined.
Keywords: G30; Q56; Q01; O16; 330; Sustainable Finance; Public Procurement; Green Public Procurement; Small and Medium-sized Companies; Innovation; Financial constraints